Optimization of composite materials with high emissivity/reflectivity for sports apparel application - Ong, Vanetta Si En (Nanyang Technological University, 2021)
Clothing act as a layer of insulation as it acts as a barrier between heat transfer and evaporation from the human skin surface to the environment. In a warm environment, additional clothing increases thermal insulation which causes rapid increase in temperature, thereby exhibiting warming effects on the body. On the other hand, clothing could exhibit cooling effects on the body as it could act as a protective layer that prevents thermal stress and radiant heat gain. This project investigates the potential of a fabric containing additives to exhibit warming and cooling effects. The additives selected to analyse in this study were based on their theoretical capabilities to exhibit these effects. The additives analysed in this project includes Mica-black, Mica-gold, BN Boron Nitride (BN), Titanium Oxide (TiO2), Silicon Carbide (SiC) and Zirconium Carbide (ZrC) of particle size at 500nm and 10μm. Fabrics were coated using Pebax as the base polymer matrix with additives. This report details the methodology to coat the fabrics. The fabric containing additives were characterized through the UV-Vis-NIR, Lamp Test with Infrared (IR) Camera, Fourier Transform Infrared Spectroscopy (FTIR) and the Bottle Test. The additives in powder form were measured using the Far Infrared Emissivity Analysis System. Two main spectrum, the Near Infrared (NIR) and Mid Infared (MIR) were studied in detailed. The NIR spectrum is closely related to solar radiation due to their similarity in wavelength. Hence, the Lamp Test with IR camera was designed to mimic the solar energy irradiating onto the fabric. The MIR is closely related to the thermal radiation from a human body due to their similarity in wavelength. Thus, the Bottle Test was designed to simulate a fabric on human. It was found that within the NIR range, BN and TiO2 are ideal materials for cooling while ZrC (500nm) and ZrC (10μm) are potential materials for warming. Results for the MIR range showed that SiC and ZrC (10 μm) are ideal materials for warming. Materials capable for cooling in the MIR were inconclusive and requires further studies.